Clays and Clay Minerals, Vol. 57, No. 2, 168–182, 2009. - Grygar, Tomas; Kadlec, Jaroslav; Zigova, Anna; Mihaljevic, Martin; Nekutova, Tereza; Lojka, Richard; Svetlik, Ivo (My University, 2009)
Copper(II) triethylenetetramine [Cu(trien)]2+ is an agent suitable for the 1-step determination of the cation exchange capacity (CEC) of many geomaterials using a procedure much less laborious than other, commonly used methods. It is also suitable for the determination of the composition of original exchangeable cations. In contrast to other common ions used for CEC analysis, the Cu(II) complex with triethylenetetramine, [Cu(trien)]2+, is specific for expandable clay minerals. The robustness of [Cu(trien)]2+ analysis was verified using reference clays, ion-exchanged reference clays, sediments, and soils. The [Cu(trien)]2+-based CEC of expandable clay minerals is not influenced significantly by ferrihydrite, goethite, manganite, birnessite, calcite, and gypsum. Birnessite, calcite, and gypsum admixtures affect the composition of the evolved cations. [Cu(trien)]2+ does not recover the entire CEC of soils (but rather that of the clay minerals only) which contain components other than clays which contribute to the CEC, e.g. soil organic matter. In a series of loess with buried paleosols and recent soils the [Cu(trien)]2+-based CEC ranged from 30 to 110% of total CEC obtained by traditional BaCl2 methods. The relative ratio of Ca to Mg, the prevailing exchangeable cations in soils and sediments in exogenic environments, are similar after [Cu(trien)]2+ and conventional BaCl2 treatments. The Ca/Mg ratio in the exchangeable fraction was used successfully for chemostratigraphic correlation of paleolacustrine sediments from a large lake in the Upper Carboniferous basins of eastern equatorial Pangaea and a series of recent flood plain sediments of the meandering Morava River in the Czech Republic. The Ca/Mg ratio obtained by [Cu(trien)]2+ analysis is proposed as a novel tool for the chemostratigraphic correlation of sediment series containing expandable clay minerals.
Chemostratigraphic Correlation Of Sediments Containing Expandable Clay Minerals Based On Ion Exchange With Cu(ii) Triethylenetetramine
gsccm57204-gry.pdf: 439KB
Keywords: Periodicals; Geology; Chemostratigraphy; Expandable Clay Minerals; Flood Sediments; Lacustrine Sediments; Smectite